2019
DOI: 10.18203/2394-6040.ijcmph20191424
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of prevalence of risk factors for coronary artery disease in a rural population in Howrah, West Bengal

Abstract: Background: Coronary artery disease (CAD) is a major cause of death globally in both developed and developing countries. Coronary artery disease which was once thought to be a disease of the urban population is now involving the rural community in an increased number. So a study of major coronary risk factors in rural communities will help to adopt various strategies particularly behavior change and communication relevant for these communities to prevent these risk factors and lower CAD related mortality and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Similar observations have been made in studies from India as well. [ 18 ] A sedentary lifestyle was more prevalent in women as compared to men, which may be attributed to some social and cultural factors in rural India. [ 19 20 28 ] Around two-thirds of participants were either having normal BMI or were underweight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations have been made in studies from India as well. [ 18 ] A sedentary lifestyle was more prevalent in women as compared to men, which may be attributed to some social and cultural factors in rural India. [ 19 20 28 ] Around two-thirds of participants were either having normal BMI or were underweight.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence in support of comprehensive interventions and relatively low cost of treatment to prevent CVD among people with diabetes, studies have shown that at a primary care practise in rural India there are critical gaps in the implementation of assessment protocol and treatment for control of risk factors of CVD amongst people with T2DM. [ 17 18 19 20 ] This study was undertaken to study CVD risk assessment and management in persons with T2DM from a rural area of central India at the primary care level.…”
Section: Introductionmentioning
confidence: 99%
“…1 Late examinations show that the commonness of patients giving coronary vein sickness (computer-aided design) old enough lesser than 45 years to be 1.2%. 2 In India, concentrates on [3][4][5] show that there has been expansion in the pervasiveness of CHD in both metropolitan and rustic populace.…”
Section: Introductionmentioning
confidence: 99%